DIRECT REVASCULIZATION OF THE MYOCARDIUM FROM LEFTSIDE MINITHORACOTOMY- MODERN PERFORMANCE OF THE OPERATION NAMED AFTER V.I. KOLESOV - G. G. Khubulava; V. N. Kravchuk; E. A. Knyazev; A. N. Shishkevich; A. S. Peleshok; A. S. Kusai; A. E. Sukharev; A. I. Lyubimov (Вестник хирургии имени И.И. Грекова)
The article provides the results of minimally invasive direct revasculization of myocardium at the period from 2012 to 2014. Given method was used in 49 interventions. There weren’t any lethal cases or myocardial infarctions. A mean hospital stay consisted of 8,6±2,7. Computer thomographic coronary bypass angiography was carried out after operation in terms of 6-48 months. The occlusion of mammary coronary shunt was revealed in 3 patients with minimally invasive revasculization of the myocardium in terms up to 48 months. There were noted a decrease of hospital stay, bleeding during surgery and in early postoperative period, duration of artificial pulmonary ventilation, length of stay in intensive care unit for this group of patients.